UNIDAD PARA SUPERVISIÓN Y CONTROL DE MEDICIÓN DE EFECTO HALL CON LABVIEW® - Hernán Rodríguez; L. Camilo Jiménez (Universitas Scientiarum)
We assembled a Hall effect and electric conductivity measuring unit that allows the determination of transportproperties in semiconductor and metal films, including the type and concentration of majority carriers and theirmobility, from measurements of Hall voltage and current. It is clear that electrons are the charge carrier in metals,however some metals such as aluminum, zinc and cadmium among others exhibit a behavior that, according to theclassical view, should be positive charge carriers (holes). In this paper we discuss Hall effect measurements in twotypes of materials: copper (Cu) and zinc (Zn). Results from measurements show that copper has a negative Hallcoefficient RH = - (0.28 ± 0.01)×10-10 m3/C and zinc has a positive coefficient RH = + (4.2 ± 0.2)×10-11 m3/C. Ourresults agree with those reported in the scientific literature. Most of the textbooks on solid state physics do notmention explicitly the reason why some metals show a positive Hall coefficient. We discuss this fact based on theirband structures.